CHI '03 Extended Abstracts on Human Factors in Computing Systems - CHI '03 2003
DOI: 10.1145/765891.766014
|View full text |Cite
|
Sign up to set email alerts
|

Design considerations for a financial management system for rural, semi-literate users

Abstract: KEYWORDSIn this paper, we describe the design process, results, and general observations obtained in designing a user interface for managing community-based micro-finance institutions in rural India. The primary users studied were semi-literate village women.We discuss our contextual study observations and conclude by presenting a grounded design approach that best leverages the existing learning patterns of the users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 0 publications
0
11
0
8
Order By: Relevance
“…[6] showed that non-literate and semi-literate subjects find it difficult to make sense of the textbased UI, and have better task-completion rates with richer multimedia. Thereafter, [7] designed mobile interfaces for such users using graphics, motivated by [2,8], and numerical digits, which are acceptable as found by [9].…”
Section: Introductionmentioning
confidence: 92%
“…[6] showed that non-literate and semi-literate subjects find it difficult to make sense of the textbased UI, and have better task-completion rates with richer multimedia. Thereafter, [7] designed mobile interfaces for such users using graphics, motivated by [2,8], and numerical digits, which are acceptable as found by [9].…”
Section: Introductionmentioning
confidence: 92%
“…Many studies report on the development and design of interfaces for low literacy individuals [33,34,24,20,18,27,14]. In order to enhance the content comprehension of the content, the studies use different kinds of media and communication modes that partially or totally replace the textual content available on the interfaces.…”
Section: Content Presentation and Interactionmentioning
confidence: 99%
“…Medhi et al [20] state that graphical representation comprehension depends on the domain that the information represents and the culture context of users. Besides the graphical representation use for presenting information, some studies describe the use of color for indexing information [18], videos tutorials [27] and tabular information for structuring data [14], among others.…”
Section: Content Presentation and Interactionmentioning
confidence: 99%
“…For instance: availability of graphic representations [5] and use of numerical symbols [11] [22]. Considering the context of automatic content generation, solutions to implement the automatic retrieval of images or other types of representation that are really significant for text understanding are highly complex.…”
Section: Related Workmentioning
confidence: 99%